Analysis of the Sustainability of Selected Targeted NGO Interventions for a Representative Small-Scale Farm Family in Ecuador - Erickson, Richard â€œJakeâ€; Bailey, DeeVon; Ward, Ruby; Allen, Karin (Journal of Reviews on Global Economics, 2013)
Linear programming techniques are used to illustrate the potential effects of targeted agricultural development interventions by non-governmental organizations. The results demonstrate the interconnection of nutrition, agricultural production, and economics in determining optimum decisions for farm families in the study area in northern Ecuador. The findings suggest that planned interventions for small-scale farmers should first consider a range of nutritional, agricultural, and economic factors before an intervention is implemented. Otherwise, planned interventions that focus on only one aspect of the family's well-being have a high probability of being unsustainable